A study on the spatial and temporal dynamics of landscape spatial patterns of different types of rural communities in Taiwan - Fuer Ning; Hui Wang; Yu-Chen Chien; Haozhang Pan; Sheng-Jung Ou (Ecological Indicators, 2023)
Climate change and urbanization are the main factors causing landscape changes not only in urban areas but also in rural communities. Rural communities have economic, cultural, social, and significant ecological value. Based on the background of environmental change, this study selects three main classes of rural communities in Taiwan as the research areas. Based on the remote sensing images from 2001 to 2020 and the survey of land use status, the land transfer matrix and landscape index method were used to analyze the landscape spatial pattern changes and driving forces of rural communities. The results revealed that (1) the land use changes of the four different types of rural communities have both common features. The growth of construction land and transportation land area is a common phenomenon, and the growth rate matches the type of rural community. Forest land or farmland is the main land cover. From the perspective of land transfer analysis, it is the mutual conversion and loss of agricultural land, forest land and other land. (2) There are differences in the landscape pattern changes of the three main classes of rural communities. The production community (Dalian) pattern is progressing steadily. The ecological community (Gangbian) pattern is progressing slowly. The process of living community pattern varies greatly, while the progress of village experience type (Shuangtan) pattern is slow. The comprehensive wealth type (Seshui) pattern is developing unevenly and at a fast pace. (3) The driving force of land use change mainly comes from the policy drive of the public sector, the spatial planning system, and community development activities. This study fills in the gaps in the development of landscape spatial patterns of different types of rural communities, and provides a reference for the formulation of regulations on the spatial planning system of rural communities in Taiwan.